Numerical Analysis of a Train-Bridge System Subjected to Earthquake and Running Safety Evaluation of Moving Train - Xun Yang; Huanhuan Wang; Xianlong Jin (Shock and Vibration)
This paper investigates the dynamic response of a train-bridge system subjected to earthquakes, and the running safety indices of the train on the bridge under earthquake are studied. Taking a long span cable-stayed bridge across the Huangpu River as an example, a full three-dimensional finite element model of the train-bridge system was established, in which the soil-bridge and rail-train interactions were considered. Parallel computing based on contact balance was utilized to deal with this large-scale numerical simulation problem. The dynamic nonlinear analysis was performed on a Hummingbird supercomputer using the finite element code LS-DYNA 971. The results show that the acceleration responses of the train subjected to an earthquake are much greater than the ones without earthquake input, and the running safety of a moving train is affected by both the earthquake intensity and the running speed of the train. The running safety of the moving train can be evaluated by the threshold curve between earthquake intensity and train speed. The proposed modeling strategies and the simulated results can give a reference prediction of the dynamic behaviour of the train-bridge subjected to an earthquake.